A rare case of arrhythmogenic right ventricular cardiomyopathy associated with LAMA2 mutation: A case report and literature review - Wang, Yue; Fang, Yibing; Zhang, Dan; Li, Yifei; Luo, Shuhua (Frontiers in Medicine, 2022)
Background: Arrhythmogenic right ventricular cardiomyopathy (ARVC) is a heritable heart muscle disorder that predominantly affects the right ventricle. Mutations in genes that encode components of desmosomes, the adhesive junctions that connect cardiomyocytes are the predominant cause of ARVC. A case with novel heterozygous mutation in the LAMA2 gene is reported here. The protein encoded by LAMA2 gene is the 𝛼 2 chain of laminin-211 protein, which establishes a stable relationship between muscle fiber membrane and extracellular matrix. We explored the potential mechanism and the relationship between the mutation and ARVC. Case Presentation: At the age of 8, the patient developed syncope and palpitation after exercise. Dynamic electrocardiogram recorded continuous premature ventricular beats and MRI showed the right ventricle was significantly enlarged and there were many localized distensions at the edge of the right ventricular wall. The patient was diagnosed with ARVC and received heart transplantation at the age of 14 due to severe heart dysfunction. The myocardial histological pathological staining revealed a large amount of fibrosis and adipose migration. Whole exome sequencing (WES) identified the heterozygous mutation in the LAMA2 gene (NM_000426.3: c.8842G>A (p.G2948S)). This is the first report of these variants. Analysis was performed on genetic disorders to reveal splice site changes and damage to protein structure. LAMA2 p.G2948S predicted unstable protein structure and impaired function. Induced pluripotent stem cell derived cardiomyocytes (iPSC-CMs) were established. RNA-seq and western blot were performed on IPSC-CMs to explore ARVC-related signaling pathway. Conclusion: This is the first case report to describe an ARVC phenotype in patients possessing a novel LAMA2 c.8842G>A (p.G2948S) mutation. Our results aid in understanding of the pathogenesis of ARVC. The molecular mechanism of LAMA2 leading to ARVC disease still needs further study.